Congruence between language proficiency and communicative abilities - Ernisa, Marzuki (Elsevier Ltd., 2013)
Reports in mass media and narratives of people in authority as well as the lay person in the street attribute unemployment of graduates to their poor communicative abilities and, in the same breath, poor proficiency in English. This raises questions for applied linguistics to address through empirical studies. This paper reports students’ views of the congruence between language proficiency and communicative abilities. The specific aspects examined are whether students conceptualise these two constructs as the same, overlapping or different; and whether students think their language proficiency and communicative ability affect their chances of employability. Semi-structured interviews were conducted with university students with different English proficiency levels. The preliminary results indicate that students see both English proficiency and communicative ability as important factors affecting their employability but they can tease apart the two constructs. The students view communicative ability as going beyond language proficiency to encompass ability to take account of other viewpoints and clarity in thought patterns during communication. The findings suggest that strategies to improve undergraduate communicative abilities cannot target English proficiency alone.